WAWASAN AL-QUR’AN DALAM PANDANGAN M. QURAISH SHIHAB DAN BUYA HAMKA - Naila Intania (Ushuluna: Jurnal Ilmu Ushuluddin, 2020)
This article discusses M. Quraish Shihab's and Buya Hamka's view on the Qur'anic perspectives. Using a descriptive analytic method, the study answers the question how the Qur'an perceives these key terms. The study finds that the Qur'an has both a sacred and profane side at the same time. Even some Muslims consider the holy side of the Qur'an to be inherent in all its dimensions. It also finds that M. Quraish Shihab discusses five dimensions of the Qur'anic perspective. Meanwhile, Hamka discusses five dimensions.